Peningkatan Keterampilan Perencanaan Keuangan Sejak Dini Untuk Membangun Kemandirian Siswa - Bayu Adi Alvinsyah; Citra Adelia; Zulfie Chaniago (CV. ITTC INDONESIA, 2026)
The low level of financial literacy and financial planning skills among vocational high school students remains a significant issue amid the increasing consumptive lifestyle of adolescents. This condition causes students to lack the ability to manage pocket money systematically, distinguish between needs and wants, and develop consistent saving habits. This community service program aims to improve early financial planning skills to foster students’ financial independence at SMK Media Informatika. The program was implemented using an educational and participatory approach, including the delivery of financial literacy materials, interactive discussions, pocket money management simulations, and practical exercises in recording income and expenses. The results indicate an improvement in students’ understanding of the importance of financial planning, their ability to prepare simple budgets, and positive behavioral changes toward more disciplined and responsible personal financial management. This activity confirms that early financial planning education plays an important role in developing students’ financial independence.